CERDAS DAN AMAN BERMEDIA DIGITAL : PENINGKATAN KESADARAN KEAMANAN SIBER DI ERA HOAKS DAN PHISHING - Arisanty, Melisa; Riady, Yasir; Anastassia Amellia Kharis, Selly; Maulidia Permatasari, Sri; Sukatmi, Sri (Education and Talent Development Center of Indonesia, 2025)
Digital safety has emerged as a critical issue that demands serious attention, particularly among younger generations. Amidst the rapid advancement of technology, adolescents' ability to safeguard their personal digital security and avoid risks such as hoaxes, phishing, cyberbullying, the spread of harmful content, and various forms of online fraud has become increasingly essential. Digital safety education plays a vital role in equipping them with the knowledge and skills necessary to confront these challenges intelligently and critically. A community engagement program conducted at SMP PGRI 1 Ciputat focused on delivering digital safety training to junior high school students, an age group situated in a crucial phase of identity and digital character formation. Evaluation results from this program revealed that 100% of participants comprehended the material presented and felt motivated to implement it in their daily digital practices. Participants demonstrated positive behavioral changes, including increased caution in sharing personal information, enhanced accuracy in verifying online content, and improved awareness in identifying and avoiding suspicious links or content. These changes also reflected greater vigilance in their overall use of digital platforms. These findings suggest that well-targeted digital safety training can serve as a strategic initiative to cultivate a generation of digitally responsible, resilient, and secure adolescents